THE REFLECTION ON THE ASSISTANCE OF QUANTIFIER AND QUALIFIER'S STEP ON EDUCATION (Fiep Bulletin - online, 2014)
The Brazilian's public educational system has demonstrated, unhappily, in its history inefficiency indications, remaining, many times, as consequence the school's failure. It's necessary that the “exacerbated” ideology to be discussed and reviewed by the teachers and that they have more certainty when they appear with the reality. From the education the human being will have clearness on their thoughts, they will be critical, putting their potentialities on a higher level. It's lamentable that education, that can do a lot to the men, has been many times not much considered and attended by politician. On this crisis' moment where the Brazilian society lives, the teacher is an indispensable part, because he is “a powerful person”, giving the concept of citizenship to the students. The educational inexistence of Philosophy on 1st and 2nd grades courses was prejudicial for all students at 70's, and today they are citizens who could participate more actively in the our country's life, if they had a solid base on philosophy on their formation, whereas this way their critical spirit and logical reasoning are developed, on its plenitude. In 1996 we had the “Lei de Diretrizes e Bases” - LDB promulgated, effectively it was when the Philosophy resurged like component of schools curriculums, on a very insipient way. There is no doubt that it was a big advancement, but the lacuna omitted in the logical thought construction of our youth will let some time to disappear. The men need to have a clear knowledge of to be or not to be, about goodness and badness, about duty and obligation, to have conditions to judge, rationally all occurrences around them. This is obtained efficiency with the structure of a good philosophical base, by letting the men elaborate concepts about the way they live, essentially, to have conditions to meet themselves, on a critical process of introspection and based on a logical ratiocination.
Keywords: education; philosophy; reflection